High-fiber diets with reduced crude protein for commercial layers - Praes, M. F. F. M. [UNESP]; Junqueira, O. M. [UNESP]; Pereira, A. A.; Filardi, R. S. [UNESP]; Duarte, K. F. [UNESP]; Sgavioli, S. [UNESP]; Alva, J. C. R. [UNESP]; Domingues, C. H. F. [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2014)
This study aimed at evaluating diets containing different fiber sources and two crude protein levels on the performance, egg quality, and nitrogen metabolism of commercial layers. In total, 392 48-wk-old Isa Brown layers were distributed according to a completely randomized experimental design in a 3x2+1 (control) factorial arrangement, resulting in seven treatments with seven replicates of eight birds each. Treatments consisted of three fiber feedstuffs (cottonseed hulls, soybean hulls, and rice hulls) and two dietary crude protein levels (12% and 16%). Cottonseed hulls associated with the high crude protein level (16%) resulted in the worst feed conversion ratio per dozen eggs. Diets with 16% crude protein resulted in the highest feed intake, egg production, egg weight, egg mass values, and improved feed conversion ratio (kg eggs/kg feed). The dietary inclusion of soybean hulls determined low yolk pigmentation, and of rice hulls, low egg specific gravity. The 16% crude protein diet with rice hulls promoted the best feed conversion ratio. Hens fed the reference diet presented higher egg mass and better feed conversion ratio per kg eggs and per dozen eggs. Hens fed the diets with low crude protein level (12%) had reduced nitrogen excretion, but presented worse egg production.
Keywords: Rice hulls; cottonseed hulls; soybean hulls; crude protein; egg production